Sexual risk behaviour among HIV-infected women in the first twelve months after delivery in South Africa. Issue 4 (4th July 2018) - Peltzer, Karl; Setswe, Geoffrey; Matseke, Gladys; Ramlagan, Shandir; Weiss, Stephen M.; Rodriguez, Violeta J.; Sifunda, Sibusiso; Cook, Ryan; Lee, Tae Kyoung; Jones, Deborah
Abstract : This study aimed to assess sexual risk behaviour and its social correlates in HIV-infected women living in rural South Africa at six and twelve months post-partum. Participants were 699 HIV-positive women recruited prenatally by systematic sampling from twelve community health centres in Mpumalanga province, South Africa (mean age = 28.4 years, SD = 5.7; married =41.1%; serodiscordant or unknown partner status = 74.9%). They self-reported on their sexual activity six to twelve months after delivery; including use of condoms and partner involvement. Generalised linear mixed models were utilised to estimate unsafe sex outcomes from a prevention of mother to child transmission (PMTCT) intervention, socio-demographic factors, disclosure, and male involvement. About 20% of sexually active women in the past week had used condoms inconsistently at six and twelve months after delivery. Moreover, 16% and 18% of the women had not used a condom at last sex and 11% and 13% had unprotected sex with HIV-uninfected or unknown-status partners following delivery at six and twelve months, respectively. Higher inconsistent condom use was likely with lower male involvement. Promotion of condom use post-partum, as well as male involvement in sexual decisions, are important for safer sex post-partum by seropositive women.